The Role of Social Support in Adolescent Resilience: A Review of Three Social Conditions - Lenny Syamsuddin; Nur Aisyah Amalia Saing; Kharisma Busura; Zafirah Manoppo; Rifky D. Pahrun (program studi psikologi, 2025)
Adolescence is a critical phase in individual development marked by complex biological, psychological, and social challenges. Resilience is an important capacity that allows adolescents to adapt positively in the face of life's pressures and difficulties. This article is a literature review that analyzes three quantitative studies on the relationship between social support and resilience in adolescents in three different social contexts: adolescents with disabilities, adolescents living in orphanages, and junior high school students. The results of the study indicate that social support, whether from family, caregivers, peers, or the school environment, has a positive and significant relationship to the level of adolescent resilience. This finding confirms that supportive interpersonal relationships are the main protective factor in forming psychological resilience. Although the intensity and source of social support vary according to social conditions, its role is very important. This study recommends strengthening contextual and adaptive social support systems, as well as the need for further research on internal factors that form adolescent resilience comprehensively and sustainably.